Wizytacje kościelne w zasobie archiwów państwowych - Krochmal, Jacek (Archiwa, Biblioteki i Muzea Kościelne, 2012)
Archive material of church provenance is stored, among others, in Polish state archives. Large collection of visitations are in state archives in Lublin, Przemyśl and the Central Archives of Historical Records in Warsaw. A large collection of Uniate visitations (Greek Catholic) stored in the State Archive of Lublin is in the fonds of Greek Catholic Consistory of Chełm (1596-1875). The fond includes directives of Uniate Bishops of Chełm on how to conduct visitations, general visitation of the diocese, visitations of deaneries and individual Uniate churches from the Diocese of Chełm (1715-1815, 1869-1870), Włodzimierz (1725-1727, 1757, 1774-1801), [Polish] Połock (1789-1790) and the Deanery of Bóbrka in the Diocese of Lviv from 1764. Historical Archive of the Orthodox and later Greek Catholic Bishopric of Przemyśl from the years 1291-1946 (the fond of the Archive of Greek Catholic Bishopric of Przemyśl) is in the State Archive in Przemyśl. There are visitations of 49 deaneries (1738-1939) and individual Uniate churches (1753-1912) from the Uniate Diocese of Przemyśl. In addition, the State Archive in Przemyśl (the fond of the Seniority of Central Galicia in Brygidau) includes visitation protocols of churches and evangelical schools from the years 1903-1910. Visitations of Roman Catholic churches and monasteries are also stored in the Central Archives of Historical Records (in the fonds of the Central Religious Authorities of Kingdom of Poland). This archive also includes the visitations of the Collegiate of Łęczyca (1810-1811), the monastery of Canons Regular in Warsaw (1767–1816), the general visitation of the Archdiocese of Warsaw (1859-1860) and visitations of the Augustian monasteries in Ciechanów, Kraków, Krasnystaw, Książ Wielki, Lublin, Orchówek, Rawa, Warsaw and Wieluń (1841-1863); and in the fond of the Orthodox Consistory of Warsaw there is a fragment of the visitation of the Orthodox Eparchy of Warsaw from 1908.